A Comparative Study on Preprocedure Ultrasound-Guided Midline Spinal Anaesthesia and Conventional Landmarks Technique - Mohamed Anwer Rifky; Mohamed Mowafy Khattab; Ayman Fathy Zeid; Ahmed Sobhy Hegab; Basmah Ahmed Abdelrahman Alrobaa (Research Developments in Medicine and Medical Science Vol. 1, 2023)
This study is aimed to effectively and accurately identify the anatomical landmarks of neuraxial blockade, in order to improve the efficacy and safety of spinal anaesthesia. Furthermore, we aimed to familiarize the anaesthesiologist with the process of using ultrasound to obtain successful neuraxial anaesthesia and analgesia, Moreover, to minimize the complications and to overcome any anticipated and unanticipated difficulty. Ultrasound (US) can be used effectively and accurately to identify the anatomical landmarks of neuraxial blockade, in order to improve the safety and efficacy of spinal anaesthesia. The study was performed in Zagazig University Hospital. Hundred and four ASA classes I and II adult cooperative patients of both sexes were scheduled for surgery in the lower part of the body under neuraxial blockade. It was discovered that there was a statistically significant difference between the PS and CL groups in terms of the number of attempts, the number of needle passes (bone hitting), the success rate of the first attempt at a dural puncture, and the overall time required to conduct the method. Ultrasound guidance enhances the success rate of midline spinal anaesthesia. It decreases the number of attempts needed, increases the success rate of a single needle pass, and shortens the time to dural puncture. More research is needed to determine the role of ultrasound-guided neuraxial block in high-risk populations such as the obese, elderly, and patients with spinal deformity. Thereby, we hope that we can incorporate ultrasound into everyday practice rather than performing separate ultrasound examinations.